Pelayanan Tuhan Yesus: Patokan Nilai Kemurnian Yang Harus Diterapkan Dalam Melayani - Rini Karnila Zai; Supriadi Oet (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2026)
Purity is the value of authenticity that has not been contaminated by anything else. In relation to service, purity is a form of sincerity and wholeheartedness in serving without having any other motivation. It emphasizes the will of God without mixing personal interests. Purity is an essential element that must be possessed by servants of God. Maintaining purity in service is not an easy task. Therefore, there is a need for a standard or benchmark in serving. Through qualitative methods that focus on literature study and phenomenological analysis, this paper elaborates and describes based on the results of the analysis of the ministry of the Lord Jesus. That is why this writing focuses on the example of the Lord Jesus which should serve as a guideline on how to serve. In facing different situations and conditions of ministry, a servant of God remains firm in maintaining purity that is not contaminated by motivations outside of Christ, namely by following His example.